We just 'SHAREit': Smartphones, data and music sharing in urban Papua New Guinea. - Crowdy, Denis; Horst, Heather A. (Australian Journal of Anthropology, 2022)
This article examines how the use of mobile phones and associated software creates and sustains regionally diverse urban communities. There is an interdependent connection between music that is highly participatory and locally relevant, and processes involved in sustaining key social relationships across a variety of groupings. Increasingly ubiquitous technologies such as mobile phones are used for musical purposes in ways that specifically put certain processes to work to sustain these social phenomena. This connects people with transnational software‐based commerce through social media, local telecommunications companies and phone manufacturers. That results in the navigation of ecologies and economies of data, hardware and software that work in local urban circumstances. In the case of data, we demonstrate how modes of exchange and reciprocity tied to social relationships exhibit similarities with informal economies of tobacco and betelnut. With social groups, the church‐based community perspective provides urban examples of communities that cross regions, and extended family networks. This ethnographic perspective shows how increasingly global technologies are used in urbanite Melanesia in ways that sustain longstanding values and practices, while also incorporating identities and associations around changing urban, national and international circumstances.